Effect Of Folic Acid And Cobalamin Supplementation On Collagen And Elastin Content In Rats' Lung Tissue: An Experimental Study (Journal of Pharmaceutical Negative Results, 2023)
Objective: The objective of this study was to investigate how the supplemental use of Folic Acid and Cobalamin impacts the levels of collagen and elastin in the lung tissue of female Sprague-Dawley rats.Study Design: Laboratory-based Experimental StudyPlace and Duration of Study: This study was carried out at the anatomy department of the CMH Multan Institute of Medical Sciences Pakistan from September 2020 to September 2021.Methodology: In this study, one hundred and twenty female Sprague-Dawley rats were used and divided into four groups. Each group comprised thirty adult female rats. Group A received a daily oral gavage of 1ml/100g of pure distilled water for four weeks. Group B1 received a daily oral gavage of 0.2mg/kg of folic acid in 1ml/100g of pure distilled water for four weeks. Group B2 underwent a daily oral gavage of 45µg/kg of cobalamin in 1ml/100g of pure distilled water over four weeks. In the case of Group B3, both folic acid (0.2mg/kg) and cobalamin (45µg/kg) were administered as supplementary doses in 1ml/100g of distilled water by oral gavage daily for four weeks. After 28 days of drug administration, the rats from all four groups were sacrificed. Sections were processed, and slides were stained with Masson’s Trichrome and aldehyde fuchsin for a light microscopic study. Data was entered and analysed via SPSS version 26.Results: The study revealed statistically significant differences in collagen and elastin content between the control and experimental groups. Specifically, the experimental groups showed an increased percentage of collagen and a decreased percentage of elastin compared to the control group.Conclusion: This experimental study shows that long-term administration of supplementary Folic Acid and Cobalamin doses brings about changes in the collagen and elastin content of lung tissue.